2005
DOI: 10.1080/13674670412331304320
|View full text |Cite
|
Sign up to set email alerts
|

The association between personality, attachment, psychological distress, church denomination and the god concept among a non-clinical sample

Abstract: The association between personality, attachment, psychological distress, church denomination and the God concept was studied among a sample of 208 subjects from the normal population. Subjects were Christians, members of an Orthodox reformed church or the Pentecostal church. Negative feelings towards God were associated with a high level of harm avoidance, insecure attachment and a high level of psychological distress. Psychological distress mediated the association between personality and attachment variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
(27 reference statements)
0
26
1
1
Order By: Relevance
“…The data structure of the two dimensions of the QGI, which results in the scales positive feelings, anxiety, anger, supportive actions, ruling/punishing actions, and passivity, shows similarities to Petersen's (1993) original structure but deviates from other studies (Eurelings-Bontekoe et al, 2005;Murken, 1998). The difference in sample may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The data structure of the two dimensions of the QGI, which results in the scales positive feelings, anxiety, anger, supportive actions, ruling/punishing actions, and passivity, shows similarities to Petersen's (1993) original structure but deviates from other studies (Eurelings-Bontekoe et al, 2005;Murken, 1998). The difference in sample may account for this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…The QGI consists of (very) short items and may be used in both non-religious and religious populations. Previous studies yielded promising results regarding the psychometric properties of the instrument (Schaap-Jonker et al, 2002;Eurelings-Bontekoe et al, 2005;Braam et al, 2007). Because it captures both the affective and cognitive aspects of the God image and thus the object-relational nature thereof (cf.…”
Section: Questionnaire God Imagementioning
confidence: 99%
See 1 more Smart Citation
“…The image of God, how people conceptualise and feel about God, has been found to be related to many aspects of subjective well-being (Braam et al, 2008b;Eurelings-Bontekoe, Hekman-Van Steeg, & Verschuur, 2005;Schaap-Jonker, Eurelings-Bontekoe, Verhagen, & Zock, 2002;Schaap-Jonker, Eurelings-Bontekoe, Zock, & Jonker, 2008;Tisdale et al, 1997). Although Rizzuto (1979) differentiated the God concept (i.e., how a person cognitively understands God) from the God image (how a person emotionally experiences God), research has found that these two are interrelated (Schaap-Jonker et al, 2008).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Generally, children and adolescents with SAD suffer from severe emotional, academic, and social damage 25 . Studies have demonstrated that assertiveness training can affect the problems with cognitive and behavioral dimensions such as anxiety, depression, social phobia, and increased social interactions 26 . Assertiveness training is meant to help people change their attitudes toward life, improve their assertiveness, express their mood and thoughts rationally and therefore boost their self-confidence.…”
Section: Introductionmentioning
confidence: 99%